Love and Belonging Needs in Dustin Thao’s You’ve Reached Sam - Izza, Vinsa Erelia (Journal of Literature, Linguistics, & Cultural Studies, 2024)
This study aims to find love and belonging needs experienced by the main character in fulfilling her needs in You’ve Reached Sam by Dustin Thao. According to Maslow (1943) the needs of love and belonging creates a human bond and humans are social creatures that crave interaction with others. The data source is a novel entitled You've Reached Sam by Dustin Thao, published in November 2021 with Wednesday Book, Thao’s You’ve Reached Sam is a novel with many characteristics of the Hierarchy of Needs. This research is in the category of literary criticism by applying a psychological approach and using Abraham Maslow's Hierarchy of Needs Theory which focuses on Love and Belonging Needs. Furthermore, the researcher uses reading technique and classifying data based on problems related to research. From this study, it is found two results of this study. First, the researcher found four forms of love and belonging needs in this novel, such as friendship relationships, family relationships, romantic relationships, and social activities. Second, the main character fulfills her love and belonging needs through mutual partners, the researcher found three people who fulfilled the main character's needs for love and belonging as told in the novel, namely from her boyfriend Sam, from her mother, and from her best friend Mika.